Acute induction of anomalous and amyloidogenic blood clotting by molecular amplification of highly substoichiometric levels of bacterial lipopolysaccharide - Pretorius, Etheresia (J R Soc Interface, 2016)
It is well known that a variety of inflammatory diseases are accompanied by hypercoagulability, and a number of more-or-less longer-term signalling pathways have been shown to be involved. In recent work, we have suggested a direct and primary role for bacterial lipopolysaccharide (LPS) in this hypercoagulability, but it seems never to have been tested directly. Here, we show that the addition of tiny concentrations (0.2 ng l(−1)) of bacterial LPS to both whole blood and platelet-poor plasma of normal, healthy donors leads to marked changes in the nature of the fibrin fibres so formed, as observed by ultrastructural and fluorescence microscopy (the latter implying that the fibrin is actually in an amyloid β-sheet-rich form that on stoichiometric grounds must occur autocatalytically). They resemble those seen in a number of inflammatory (and also amyloid) diseases, consistent with an involvement of LPS in their aetiology. These changes are mirrored by changes in their viscoelastic properties as measured by thromboelastography. As the terminal stages of coagulation involve the polymerization of fibrinogen into fibrin fibres, we tested whether LPS would bind to fibrinogen directly. We demonstrated this using isothermal calorimetry. Finally, we show that these changes in fibre structure are mirrored when the experiment is done simply with purified fibrinogen and thrombin (±0.2 ng l(−1) LPS). This ratio of concentrations of LPS : fibrinogen in vivo represents a molecular amplification by the LPS of more than 10(8)-fold, a number that is probably unparalleled in biology. The observation of a direct effect of such highly substoichiometric amounts of LPS on both fibrinogen and coagulation can account for the role of very small numbers of dormant bacteria in disease progression in a great many inflammatory conditions, and opens up this process to further mechanistic analysis and possible treatment.